Stem Cells Engineered During Different Stages of Reprogramming Reveal Varying Therapeutic Efficacies. (1st April 2018) - Bhere, Deepak; Khajuria, Rajiv Kumar; Hendriks, William T.; Bandyopadhyay, Antara; Bagci-Onder, Tugba; Shah, Khalid
Abstract : Stem cells are emerging as promising treatment strategies for several brain disorders and pathologies. In this study, we explored the potential of creating induced pluripotent stem cell-derived neural stem cells (ipNSC) by using either unmodified or gene-modified somatic cells and tested their fate and therapeutic efficacies in vitro and in vivo. We show that cells engineered in somatic state lose transgene-expression during the neural induction process, which is partially restored by histone deacetylase inhibitor treatment whereas cells engineered at the ipNSC state have sustained expression of transgenes. In vivo, bimodal mouse and human ipNSCs engineered to express tumor specific death-receptor ligand and suicide-inducing therapeutic proteins have profound anti-tumor efficacy when encapsulated in synthetic extracellular matrix and transplanted in mouse models of resected-glioblastoma. This study provides insights into using somatic cells for treating CNS disorders and presents a receptor-targeted cancer therapeutic approach for brain tumors. Abstract : Flow diagram revealing the steps involved in converting patient derived fibroblasts into engineered therapeutic neural stem cells to treat brain tumors and present a promising potential for application in numerous malignancies.